APPLICATION OF ADAPTIVE FILTERS IN MODERN SIMULATION OF DYNAMIC CONTROL OBJECTS - Zaripova , Shahlo (Innovatsion texnologiyalar, 2024)
The article discusses the use of adaptive filters in modern modeling of dynamic control objects. Presents a type of adaptive filtering of digital signal processing in modern electronic equipment. Adaptive signal processing, which refers to adaptive filtering, should be used in cases where filters with specified parameters are not able to perform the task. The article provides general information about the main types of adaptive filtering algorithms, means of modeling them, as well as examples of the implementation of adaptive filters using modern digital signal processors. The availability of various adaptive filtering algorithms allows electronic equipment developers to make trade-offs between computational complexity and efficiency when developing or using adaptive filters.